2012
DOI: 10.1289/ehp.1104079
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Modifying Effects of Metallothionein Single-Nucleotide Polymorphisms on the Association between Mercury Exposure and Biomarker Levels

Abstract: Background: Recent studies have suggested that several genes that mediate mercury metabolism are polymorphic in humans.Objective: We hypothesized that single-nucleotide polymorphisms (SNPs) in metallothionein (MT) genes may underlie interindividual differences in mercury biomarker levels. We studied the potential modifying effects of MT SNPs on mercury exposure–biomarker relationships.Methods: We measured total mercury in urine and hair samples of 515 dental professionals. We also surveyed occupational and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 37 publications
6
62
0
Order By: Relevance
“…Two MT isoforms, MT1 and MT2, in particular, are implicated in the dispersal and storage of Hg in the CNS (West et al, 2008). Studies in humans have suggested that SNPs of these MT isoforms, MT1M (rs2270837) and MT2A (rs10636), affect Hg body burden, and therefore potentially modify the adverse effects of Hg on neurobehavioral functions (Gundacker et al, 2007; Wang et al, 2012). Testing this hypothesis in children, we observed numerous significant adverse effects, particularly in relation to chronic Hg exposure, among boys genotyped as HetMut for either MT1M or MT2A, occurring principally within the domains of Visual Spatial acuity and Learning & Memory, but also on tests of Attention and Motor function (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two MT isoforms, MT1 and MT2, in particular, are implicated in the dispersal and storage of Hg in the CNS (West et al, 2008). Studies in humans have suggested that SNPs of these MT isoforms, MT1M (rs2270837) and MT2A (rs10636), affect Hg body burden, and therefore potentially modify the adverse effects of Hg on neurobehavioral functions (Gundacker et al, 2007; Wang et al, 2012). Testing this hypothesis in children, we observed numerous significant adverse effects, particularly in relation to chronic Hg exposure, among boys genotyped as HetMut for either MT1M or MT2A, occurring principally within the domains of Visual Spatial acuity and Learning & Memory, but also on tests of Attention and Motor function (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, Hg 2+ directly impairs the enzymatic activity of CPOX4 (Li and Woods, 2009) and also likely inhibits preferentially the S-containing met forms of the COMT val158met enzyme and the BDNF val66met protein product, both of which play critical roles in neurologic development (Barnett et al, 2009; Burkhalter et al, 2003). Moreover, genetic variants affecting Hg toxicokinetics, e.g., MT1M, MT2A, GSTT1 (Wang et al, 2012), might predispose children to higher concentrations of Hg in critical brain regions than would occur in adults with comparable exposures. Such effects directed against components of the developing central nervous system could underlie the preferential susceptibility of children and adolescents with these genotypes to the adverse neurologic effects of Hg exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-level exposures from mercury-containing dental amalgam result in urine Hg levels that overlap those of the US general population (Wang et al 2012). Moreover, many dentists and dental technicians have occupational exposures to other neurotoxic agents, including nitrous oxide (National Institute for Occupational Safety and Health (NIOSH) 2015), an anesthetic associated with impaired neurobehavioral performance (Lucchini et al 1996) and increased risk of neurological disease (Cohen et al 1980), and methyl methacrylate, a monomer widely used in dentistry that has been associated with sensorimotor neuropathy (Verkkala et al 1983; Seppalainen and Rajaniemi 1984; Rajaniemi 1986).…”
Section: Methodsmentioning
confidence: 99%
“…Cd exposure results in pathological conditions in the liver, testis, brain, and nervous system, kidney, spleen, and bone marrow, locations that have been shown to express MT upon induction. Its exposure can also lead to apoptosis in testes of rat, mouse liver, and human T-cells [16]. Having re gistered continuously decreasing MT concentrations in the brain under two different low doses of Cd, we observed that MT plays a vital role in heavy metal regulation.…”
Section: оригінальні дослідженняmentioning
confidence: 75%